2018
DOI: 10.1089/cyber.2016.0727
|View full text |Cite
|
Sign up to set email alerts
|

Cyber-Dependent Crime Victimization: The Same Risk for Everyone?

Abstract: The Internet has simplified daily life activities. However, besides its comfortability, the Internet also presents the risk of victimization by several kinds of crimes. The present article addresses the question of which factors influence cyber-dependent crime and how they vary between three kinds of cyber-dependent offences: malware infection, ransomware infection, and misuse of personal data. According to the Routine Activity Approach, it is assumed that crime is determined by a motivated offender, the behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 11 publications
0
17
0
2
Order By: Relevance
“…Näsi et al, 2015Näsi et al, , 2017van Wilsem, 2013), and that males have commonly been found to be more likely victims of other types of online offences (e.g. Bergmann et al, 2018;Milani et al, 2020;Näsi et al, 2015). Education and financial status do not appear to be more notable factors regarding online victimisation than they do in relation to offline crime.…”
Section: Cybercrime Victimisation and Risk Factorsmentioning
confidence: 86%
See 3 more Smart Citations
“…Näsi et al, 2015Näsi et al, , 2017van Wilsem, 2013), and that males have commonly been found to be more likely victims of other types of online offences (e.g. Bergmann et al, 2018;Milani et al, 2020;Näsi et al, 2015). Education and financial status do not appear to be more notable factors regarding online victimisation than they do in relation to offline crime.…”
Section: Cybercrime Victimisation and Risk Factorsmentioning
confidence: 86%
“…For our analysis, firstly, we provide descriptive statistics of all the victimisation items, secondly, estimate logistic regression models, and thirdly Poisson regression models for the selected outcomes. The estimates from the logistic regression models are reported in average marginal effects (AME) (see also Bergmann et al, 2018). The reason for this is to give a more descriptive picture of the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existing literature on cybercrime and victimisation largely fails to differentiate between distinct types of crimes (Bergmann et al, 2017). Despite the lack of a typology distinguishing cybercrime, risks and consequences, research suggests that various online activities are associated with specific types of cybercrime experiences (Bergmann et al, 2017; Leukfeldt and Yar, 2016). Further research may enable the identification of objectively risky online behaviour profiles based on the association between engagement in an activity and the likelihood of experiencing specific forms of victimisation.…”
Section: Introductionmentioning
confidence: 99%